The dynamic impact of new subway stations on housing prices in Hangzhou under the background of subway expansion(地铁扩张背景下新建站点对杭州市住房价格的动态影响) - 陈思洁(CHEN Sijie); 张凌(ZHANG Ling) (Zhejiang Daxue xuebao. Lixue ban)
This paper adopts a time-varying DID model, taking Hangzhou for case study, to explore the dynamic effects of newly built subway stations on housing prices under the background of subway expansion. The main conclusions are as follows: (1) In the process of subway expansion, the prices of surrounding houses begin to rise as soon as the concerned line plan is announced, and it still produces a value-added effect after construction and opening, but the influence scope after opening is reduced to 1 kilometer around the stations. (2) There is spatial heterogeneity in the impact of subway stations on the surrounding housing prices, which is manifested that suburban stations have a greater premium effect on the surrounding housing, while the premium effect of urban stations is limited to 500 m after opening. (3) Transfer stations can provide greater accessibility benefits than conventional stations. (4) The expansion of the subway will bring about a greater increase in the value of surrounding properties. With the continuous construction and expansion of subway lines and the gradual popularization of subway houses, the planning and opening of new stations still have a significant value-added effect on surrounding housing prices, but the radiation range has narrowed.采用多时点双重差分（DID）模型，以杭州市为例，探讨地铁扩张背景下新建地铁站点对住房价格影响的动态效应。主要结论有：（1）在地铁扩张过程中，线路规划公布后周边住房价格即开始提升，且在建设期和开通后继续具有增值效应，但开通后的影响范围缩减至站点周边1 km以内。（2）地铁站点对周边住房价格的影响存在空间异质性，位于非主城区的地铁站点对周边住房的溢价效应更大，而位于主城区的地铁站点开通后仅在其500 m范围内具有溢价效应。（3）与常规站相比，换乘站的可达性效应更大。（4）地铁规模的扩大会推动周边住房价格上涨。随着地铁线路的扩张以及地铁房的普及，地铁站点的规划、开通对周边住房价格的增值效应仍显著，但辐射范围缩小。